The Influence Of Personal Values And Job Characteristics On Professional Commitment With Ethical Behavior As An Intervening Variable At The KPP Pratama Bangkalan - Isnaeni, Mochamad; Sundjoto; Rahayu, Sri (International Publisher (YAPENBI), 2023)
The Directorate General of Taxes (DGT) is one of the state institutions that has the main task of collecting state revenue through taxes and in carrying out its duties the Directorate General of Taxes is required to always be ready to face all challenges. To achieve the tax revenue target as set in the state budget, it is absolutely necessary to have a high commitment to work professionally from each employee. One of the things that often becomes a major issue related to taxation is the ethics and professionalism of tax employees. This study aims to examine the influence between personal values and job characteristics on professional commitment with ethical behavior as an intervening variable at KPP Pratama Bangkalan. The sample in this study were 79 employees at KPP Pratama Bangkalan. The analytical tool used in this research is multiple linear regression. The results showed that personal values affect ethical behavior, personal values affect professional commitment, job characteristics have no effect on ethical behavior, job characteristics affect professional commitment, ethical behavior can mediate the effect of personal values on professional commitment, and ethical behavior cannot mediate the effect of job characteristics on professional commitment.